2013
DOI: 10.1007/s10900-013-9756-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Perceived Risk of Developing Cancer Among African-Americans in South Los Angeles

Abstract: Background There are differences in cancer-risk perception among racial/ethnic groups that may affect health risk behaviors. Methods Using a community partnered-participatory research approach, we conducted a survey on cancer screening, risk behaviors, and related knowledge/attitudes within 11 churches in South Los Angeles with predominantly African-American parishioners. This analysis examines correlates of perceived risk of developing cancer among 755African American adults. Results Almost 15% of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…She reached 755 African-American congregants, outperforming traditional faculty in recruitment with this population. 25 Ms. Jones provided leadership and expertise on a study that found that using community engagement approach for implementing quality improvement programs for depression with community-based service providers resulted in improved mental health, physical activity, and homelessness risk factors for study participants. 26 The Los Angeles County Department of Mental Health featured this study in its 2015 African-American Mental Health Workshop 27 and has made the presentation available on its website as a resource.…”
Section: Discussionmentioning
confidence: 99%
“…She reached 755 African-American congregants, outperforming traditional faculty in recruitment with this population. 25 Ms. Jones provided leadership and expertise on a study that found that using community engagement approach for implementing quality improvement programs for depression with community-based service providers resulted in improved mental health, physical activity, and homelessness risk factors for study participants. 26 The Los Angeles County Department of Mental Health featured this study in its 2015 African-American Mental Health Workshop 27 and has made the presentation available on its website as a resource.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study design have been described previously. 19 In brief, this study was planned by a team of academic and community investigators. Utilizing a communitypartnered participatory approach pioneered by L. Jones and colleagues, 20 a survey instrument was developed.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the items were adapted from prior surveys. 17,18 An English language draft questionnaire was translated into Spanish and back-translated into English by different bi-lingual individuals.…”
Section: Assessment Instrumentmentioning
confidence: 99%